2019
DOI: 10.17261/pressacademia.2019.1034
|View full text |Cite
|
Sign up to set email alerts
|

Customer experience quality dimensions in health care: Perspectives of industry experts

Abstract: Purpose -In an era which patients are acting as consumers, this paper aims to emphasize the importance of patient experience and reveal the key concepts for patient experience according to industry experts' perspectives. Seven key concepts are presented as the critical dimensions of patient experience. Methodology -A qualitative study is designed and conducted following the phenomenological approach. 15 experts are interviewed about the patient experience and content analysis is conducted to the answers in tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…The results showed that foreign customers' perceptions consist of four dimensions of the employee behavior, physical environment, functionality and value. Ozcelik and Burnaz (2019) determined the dimensions of customer experience in healthcare from the perspective of industry experts. They found that touchpoint diversity, provider and patient type, function, preference, interaction, psychology, and environment to be patient experience dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that foreign customers' perceptions consist of four dimensions of the employee behavior, physical environment, functionality and value. Ozcelik and Burnaz (2019) determined the dimensions of customer experience in healthcare from the perspective of industry experts. They found that touchpoint diversity, provider and patient type, function, preference, interaction, psychology, and environment to be patient experience dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…In this, so-called "Age of Experience", the harsh global competition changes harshly and swiftly [1][2][3]. Healthcare organizations are increasingly realizing the importance of focusing on the healthcare experience delivered to patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…Our study aims to create a model for community pharmacies providing professional pharmacy services for explaining from the perspective of experiential marketing. In this context, a structural equation model to explain Patient Experience (PX) in Community Pharmacies which was developed before in hospitals [3,9] The originality of this study lies in being the first study that focused on the conceptual model showing that patient experience through the lens of experiential marketing terms in the community pharmacies.…”
Section: Introductionmentioning
confidence: 99%